Aptamer-immobilized bone-targeting nanoparticles in situ reduce sclerostin for osteoporosis treatment. (August 2022) - Niu, Yuting; Yang, Yang; Yang, Zhen; Wang, Xu; Zhang, Ping; Lv, Longwei; Liu, Yan; Liu, Yunsong; Zhou, Yongsheng
Abstract: Bone-targeted drug delivery to reduce systemic complications and maintain sufficient doses in bone tissues is the main challenge for osteoporosis treatment. Here, we develop a novel, and simply synthesized bone-targeting nanomedicine (DNA-MSN, DNAM) containing a PEGylated dendritic mesoporous silica nanoparticle (MSN) core ( 65 nm) and an anti-sclerostin aptamer (Aptscl56) layer, to treat osteoporosis. The nanoparticle core protects the immobilized Aptscl56 from rapid nuclease degradation and renal filtration, prolonging in vivo half-lives. The DNAM-immobilized Aptscl56 layer exhibits dual functions to direct bone-attachment of ovariectomized mice, due to the interaction between phosphate groups in DNA aptamer Aptscl56 and bone calcium in hydroxyapatites, and to in situ capture sclerostin with picomolar affinities. Moreover, we show DNAM significantly reverses the serum level of sclerostin and osteoporotic bone loss to a normal level, improving bone histomorphology parameters and mechanical properties in the femur, and recovering serum levels of bone turnover markers, without systemic toxicity. Notably, the therapeutic effect of DNAM is superior to the "gold standard" drug alendronate, and the systemic dose of DNAM-immobilized Aptscl56 is only 25% of free Aptscl56. The present study provides insights into the regulation of unwanted circulating biohazards and represents a promising approach to deliver nanomedicines to treat osteoporosis. Graphical Abstract: ga1 Highlights: A promising nanomedicine of DNAM was produced to reduce sclerostin and treat osteoporosis. An anti-sclerostin DNA aptamer layer, Aptscl56, targeted bones and captured sclerostin. MSN cores protected DNAM-attached Aptscl56 from renal filtration and degradation. DNAM rescued osteoporosis, superior to the "gold standard" drug alendronate.